Alginate/gelatin mineralized hydrogel modified by multilayers electrospun membrane of cellulose: Preparation, properties and in-vitro degradation. (October 2021) - Jing, Yidan; Mahmud, Sakil; Wu, Chenfeng; Zhang, Xiaomin; Su, Shengpei; Zhu, Jin
Highlights: SAG hydrogel was modified by the multilayer electrospinning membrane of cellulose. SAG-C showed excellent mechanical and biocompatibility properties. M-SAG-C showed better mechanical and biocompatibility properties due to mineralization. No hazardous materials were used in obedience to the features of green and sustainable chemistry. Abstract: Sodium alginate (SA) hydrogel has a broad prospect in tissue engineering and other biomedical fields due to its biocompatibility. However, the single SA hydrogel has shown poor mechanical properties and cell adhesion, which seriously limited its application and development in tissue engineering scaffolds. Herein, the SA/gelatin (SAG) hydrogel was modified by the multilayers electrospinning membrane of cellulose (SAG-C). It showed excellent mechanical properties when the layer number of electrospinning membrane got to three. After mineralization (M-SAG-C), the mechanical and biocompatible properties have been further improved. The SAG, SAG-C, and M-SAG-C series hydrogels all had good water retention, swelling rates, and good degradation performance. The fluorescence staining and cell proliferation experiments showed that M-SAG, SAG-C, and M-SAG-C hydrogel materials had no apparent cytotoxicity. Simultaneously, the introduction of bone-like apatite in the M-SAG-C hydrogel material allowed the cells to have better adhesion and proliferation ability on the composite surface. And the higher the degree of mineralization, the better the cell compatibility of the hydrogel material. Therefore, such hydrogels had excellent biocompatibility and mechanical properties, which could be widely used in tissue engineering.